THE INFLUENCE OF OCCUPATIONAL SAFETY AND HEALTH ON JOB SATISFACTION OF EMPLOYEES OF THE PORT MASTER AND PORT AUTHORITY OFFICE CLASS III KUALA TANJUNG - Etika Sri Mardiandani; Agus Triyanda Sinaga; Eka Mayastika Sinaga; Willy Cahyadi (CV. Radja Publika, 2025)
This study aims to determine the effect of occupational safety and health on employee job satisfaction at the Office of the Harbourmaster and Port Authority Class III Kuala Tanjung. The population in this study consisted of 57 employees. The data analysis techniques used include classical assumption tests (normality test, multicollinearity test, and heteroscedasticity test), multiple linear regression analysis to measure the effect of independent variables on the dependent variable, and hypothesis testing through t-test and F-test. The results showed that partially, occupational safety has a significant effect on employee job satisfaction. Likewise, occupational health also has a significant effect on job satisfaction. Simultaneously, occupational safety and health have a significant effect on employee job satisfaction at the Office of the Harbourmaster and Port Authority Class III Kuala Tanjung. These findings highlight the importance of implementing proper occupational safety and health standards to enhance employee satisfaction.